Teacher Talk in Vocational High School Context âDoes it Matter?â - Nuraini, Kristi; Hamim, Miftahul (Proceeding of International Conference on Teacher Training and Education, 2016)
The research was conducted as a pilot observation study focusing on three aspects of teacher talk in asecondary level L2 of a vocational high school class. The relevance of the investigation lays in the factthat teaching ESP in Indonesia is gaining more and more important. Teacher talk has widely beeninvestigated in EFL classrooms but little is known about the characteristics of teacher and student talk inthe ESP context.Â  Firstly, the investigation aims to shed light on the ratio of teacher talk to student talk,and secondly, it aims to gain an insight into the role of the mother-tongue in the teaching process. Thefindings indicate that the amount of teacher and student talk in the ESP classroom is similar to empiricaldata obtained in L2 EFL settings. The use of the mother-tongue was perceived to be exaggerated and insome instances unjustified. It is believed that the results of the study will enable ESP teachers to plantheir classroom talk more consciously and obtain a more critical stance when analysing their own talk.